MTOR independent alteration in ULK1 Ser758 phosphorylation following chronic LRRK2 kinase inhibition. Issue 2 (20th April 2018) - Manzoni, Claudia; Mamais, Adamantios; Dihanich, Sybille; Soutar, Marc P.M.; Plun-Favreau, Helene; Bandopadhyay, Rina; Abeti, Rosella; Giunti, Paola; Hardy, John; R. Cookson, Mark; Tooze, Sharon A.; Lewis, Patrick A.
Abstract : Unc-51 Like Kinase 1 (ULK1) is a critical regulator of the biogenesis of autophagosomes, the central component of the catabolic macroautophagy pathway. Regulation of ULK1 activity is dependent upon several phosphorylation events acting to repress or activate the enzymatic function of this protein. Phosphorylation of Ser758 ULK1 has been linked to repression of autophagosome biogenesis and was thought to be exclusively dependent upon mTOR complex 1 kinase activity. In the present study, a novel regulation of Ser758 ULK1 phosphorylation is reported following prolonged inhibition of the Parkinson's disease linked protein leucine rich repeat kinase 2 (LRRK2). Here, modulation of Ser758 ULK1 phosphorylation following LRRK2 inhibition is decoupled from the repression of autophagosome biogenesis and independent of mTOR complex 1 activity.